Determinants of farmers' choice to use irrigation systems: The case of northern Ethiopia - Gebrekidan, Berhe Girmay; Abbay, Aradom Gebrekidan; Azadi, Hossein; Viira, Ants‐Hannes; Tanaskovik, Vjekoslav; Janeska Stamenkovska, Ivana; Nacka, Marina; Scheffran, Jürgen (Wiley, 2022)
AbstractClimate change is thought to be having a negative impact on Africa's agricultural industry. Smallholder farmers who depend heavily on agriculture are more severely affected by climate change. Droughts and the depletion of water resources are two examples of how climate change affects production. Therefore, it is necessary to take steps to reduce the negative effects of climate change in Ethiopia on smallholder farmers in particular and agriculture in general. Therefore, the purpose of this analysis was to identify the factors that affect the increase in irrigation efficiency among farmers in northern Ethiopia. A total of 194 farmers were picked at random and questioned using semi‐structured questionnaires. Out of the 18 explanatory variables hypothesized to analyse the preference of farmers for using irrigation in the study area, only 13 were considered important. Of these 13 significant explanatory variables, 4 including health status, labour force members, availability of labour and perception of the advantage of using agricultural inputs were statistically significant with farmers' choice of irrigation.